Reducing antibiotic use in uncomplicated urinary tract infections in adult women: a systematic review and individual participant data meta-analysis. (December 2022) - Kaußner, Yvonne; Röver, Christian; Heinz, Judith; Hummers, Eva; Debray, Thomas P.A.; Hay, Alastair D.; Heytens, Stefan; Vik, Ingvild; Little, Paul; Moore, Michael; Stuart, Beth; Wagenlehner, Florian; et al.
Abstract: Background: Randomised controlled trials (RCTs) investigated analgesics, herbal formulations, delayed prescription of antibiotics, and placebo to prevent overprescription of antibiotics in women with uncomplicated urinary tract infections (uUTI). Objectives: To estimate the effect of these strategies and to identify symptoms, signs, or other factors that indicate a benefit from these strategies. Data sources: MEDLINE, EMBASE, Web of Science, LILACS, Cochrane Database of Systematic Reviews and of Controlled Trials, and ClinicalTrials. Study eligibility criteria, participants and interventions: RCTs investigating any strategies to reduce antibiotics vs. immediate antibiotics in adult women with uUTI in primary care. Methods: We extracted individual participant data (IPD) if available, otherwise aggregate data (AD). Bayesian random-effects meta-analysis of the AD was used for pairwise comparisons. Candidate moderators and prognostic indicators of treatment effects were investigated using generalised linear mixed models based on IPD. Results: We analysed IPD of 3524 patients from eight RCTs and AD of 78 patients. Non-antibiotic strategies increased the rates of incomplete recovery (OR 3.0; 95% credible interval (CrI), 1.7–5.5; Bayesian p-value (pB ) = 0.0017; τ = 0.6), subsequent antibiotic treatment (OR 3.5; 95% CrI, 2.1–5.8; pB = 0.0003) and pyelonephritis (OR 5.6; 95% CrI, 2.3–13.9; pB = 0.0003). Conversely, they decreased overall antibiotic use by 63%. Patients positive for urinary erythrocytes and urine culture were at increased risk for incomplete recovery (OR 4.7; 95% CrI, 2.1–10.8; pB = 0.0010), but no difference was apparent where both were negative (OR 0.8; 95% CrI, 0.3–2.0; pB = 0.667). In patients treated using non-antibiotic strategies, urinary erythrocytes and positive urine culture were independent prognostic indicators for subsequent antibiotic treatment and pyelonephritis. Conclusions: Compared to immediate antibiotics, non-antibiotic strategies reduce overall antibiotic use but result in poorer clinical outcomes. The presence of erythrocytes and tests to confirm bacteria in urine could be used to target antibiotic prescribing.